Pengaruh kehidupan anak rantau di ma'had terhadap kemampuan mengatur keuangan: Studi kasus pada ma'had Sunan Ampel Al-Aly - Mustofa, Laila (Maliki Interdisciplinary Journal, 2026)
The purpose of this study is to examine how the lives of students living far from home (anak rantau) in Ma’had Sunan Ampel Al-Aly influence their ability to manage personal finances. The research is grounded in the fact that students residing in the Ma’had environment are responsible for their own expenses, making financial management skills essential for successful dormitory life. This study employs a descriptive quantitative approach with 23 students as respondents. A 5-point Likert scale questionnaire was used to assess their financial management abilities. The results indicate that most respondents fall into the high-ability category, with the following score distribution: 9 students selected score 5, 8 selected score 4, and 6 selected score 3. The calculated mean score is 4.13, suggesting that life in the Ma’had positively influences the financial management capabilities of students living away from home. The study finds that the structured routines, culture of simplicity, and religious environment of the Ma’had contribute to more disciplined and focused spending habits. These findings may serve as a foundation for developing financial literacy programs tailored for Ma’had students.